Eksplorasi Bahan Ajar Interaktif Berbasis Google Sites dalam Pembelajaran Menulis Deskripsi bagi Siswa Kelas VII SMP/MTs - Linda Rizkika Sekarsari; Anwar Efendi; Ari Kusmiatun (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2026)
Descriptive writing in Phase D requires students to observe objects, select relevant details, and organize ideas coherently. In practice, the teaching materials available in schools remain fragmented across textbooks, worksheets, slides, and sample texts, and therefore do not form a single sequence that guides students through the writing process. This study maps teachers' and students' needs for Google Sites-based interactive teaching materials as the basis for subsequent product development. It was designed as a preliminary needs analysis situated in the Analyze phase of the ADDIE model, employing a descriptive qualitative approach supported by a quantitative survey. Data were gathered through questionnaires completed by 177 seventh-grade students and eight Indonesian language teachers across ten public and private junior secondary schools and madrasahs in the Special Region of Yogyakarta, supplemented by document analysis. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña, with source and method triangulation. The findings reveal a paradox of need: most students and teachers rated their learning resources as appropriate (90.4% and 87.5%), yet only some actually used materials designed specifically for writing (69.5% and 62.5%), while open-ended responses uncovered concrete writing difficulties among 81.9% of the students. The availability of learning resources therefore does not amount to the availability of tools that guide the writing process. The most prominent need concerns explicit step-by-step writing guidance and visual support as observational stimuli rather than attractive presentation. The novelty of this study lies in formulating an empirically grounded needs framework, integrated, sequential, multimodal, and contextual, that positions Google Sites as an organizer of the writing process rather than a repository of materials.